Hemocyanins from Helix and Rapana Snails Exhibit in Vitro Antitumor Effects in Human Colorectal Adenocarcinoma - Ani Georgieva; Katerina Todorova; Ivan Iliev; Valeriya Dilcheva; Ivelin Vladov; Svetlozara Petkova; Reneta Toshkova; Lyudmila Velkova; Aleksandar Dolashki; Pavlina Dolashka (Biomedicines, 2020)
Hemocyanins are oxygen-transporting glycoproteins in the hemolymph of arthropods and mollusks that attract scientific interest with their diverse biological activities and potential applications in pharmacy and medicine. The aim of the present study was to assess the in vitro antitumor activity of hemocyanins isolated from marine snail Rapana venosa (RvH) and garden snails Helix lucorum (HlH) and Helix aspersa (HaH), as well the mucus of H. aspersa snails, in the HT-29 human colorectal carcinoma cell line. The effects of the hemocyanins on the cell viability and proliferation were analyzed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and the alterations in the tumor cell morphology were examined by fluorescent and transmission electron microscopy. The results of the MTT assay showed that the mucus and α-subunit of hemocyanin from the snail H. aspersa had the most significant antiproliferative activity of the tested samples. Cytomorphological analysis revealed that the observed antitumor effects were associated with induction of apoptosis in the tumor cells. The presented data indicate that hemocyanins and mucus from H. aspersa have an antineoplastic activity and potential for development of novel therapeutics for treatment of colorectal carcinoma.